Case Report: Surgical correction of pulmonary artery sling causing tracheal obstruction in infancy: rapid and complete recovery - Sicim, Hüseyin; Velez, Daniel A.; Alaeddine, Mohamad (Frontiers in Cardiovascular Medicine, 2025)
Pulmonary artery sling (PAS) is an uncommon congenital anomaly in which the left pulmonary artery (LPA) originates abnormally from the posterior aspect of the right pulmonary artery (RPA). The LPA then traverses between the trachea and esophagus, resulting in compression of the lower trachea. This compression can lead to respiratory symptoms, including wheezing and stridor, and in some cases, airway obstruction. In addition, bronchial compression—commonly affecting the right bronchus—can result in air trapping, pneumonia, and atelectasis. In this report, we present postoperative rapid relief of a symptomatic case in which LPA transection and reimplantation to the main pulmonary artery were performed successfully on cardiopulmonary bypass.